METASTATIC BREAST CANCER TO THE UTERINE CERVIX MIMICKING A GIANT CERVICAL LEIOMYOMA - HORIKAWA, MAI (Nagoya J Med Sci, 2012)
Metastasis to the uterine cervix is a complication of breast cancer that is not commonly known. Detection of cervical metastasis before the diagnosis of the primary tumor is even rarer. The present report describes a case of a 52-year-old woman who had a large cervical tumor appearing as a leiomyoma. She underwent a total abdominal hysterectomy with bilateral salpingo-oophorectomy. Histopathological examination of the cervical tumor showed patterns characteristic of invasive lobular carcinoma of the breast, leading to the discovery of the primary in the left breast. She subsequently underwent mastectomy, hormone therapy and chemotherapy, and is alive at 7-year follow-up.